Permanent form of junctional reciprocating tachycardia and tachycardia-induced cardiomyopathy treated by catheter ablation: a case report - Semizel, Evren; Ayabakan, Canan; Ceviz, Naci; Çeliker, Alpay (The Turkish Journal of Pediatrics, 2003)
The permanent form of junctional reciprocating tachycardia (PJRT) is usually refractory to drug therapy, and these patients are at risk of developing tachycardia-induced cardiomyopathy. The electrocardiogram insribes inverted P waves in leads 2, 3, aVF as well as left lateral leads, along with a P-R interval shorter than R-P interval during the tachycardia. This report describes a three-year-old male patient with PJRT who underwent successful radiofrequency catheter ablation (RFA) of accessory pathway. On transthoracic echocardiography of patient, decreased ventricular systolic function was observed. RFA was performed by applying radiofrequency pulses. Echocardiograms of the patient, two months after catheter ablation, demonstrated progressive improvement of ventricular function. Transcatheter radiofrequency ablation of accessory pathways in patients with PJRT is an effective, and possibly preferable, form of treatment, especially in cases of tachycardia refractory to multiple pharmacologic treatments or when left ventricular dysfunction is present.